Peran Anggota DPR Perempuan dalam Upaya Pengarusutamaan Gender pada Fasilitas Publik Pengaturan Lahan Parkir Berbasis Gender di Kota Depok - Lia Fauziyyah Ahmad; Rosdiana Rosdiana; Atep Abdurofiq (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
This study aims to determine the role of women DPRD in overseeing parking policies between women and men and to understand the impact of the role of women DPRD on public facilities in gender mainstreaming efforts in Depok City, especially in hospitals, shopping centers, and Depok City Hall in 2019 The parking lot policy as gender-responsive is a strategic step to seek gender mainstreaming. The research method used in this study uses a sociological empirical approach through empirical or non-doctrinal legal research with qualitative data, which observes policies and is analyzed through application to concrete events. Through a study of parking area policies in Depok City, it is corroborated by the results of interviews with female DPRD members in Depok City for the 2019-2024 period, visitors, and parking managers in Depok City. The results of the study indicate that the role of women's DPRD is considered capable of maintaining gender-responsive stability and achieving equitable justice for the community, both men and women.